Outcome assessment of a Global Fund grant for tuberculosis control at the district level in rural Cameroon - Yumo, Habakkuk Azinyui; Mbanya, D.; Kuaban, C.; Neuhann, Florian (The international journal of tuberculosis and lung disease, 2011)
SETTING: Batibo District Hospital (BDH), North-West Cameroon. OBJECTIVE: To assess the outcome of the implementation of the Global Fund (GF) Grant Round 3 for tuberculosis (TB) control at the district level. DESIGN: A retrospective study for the period 2003-2008 comparing TB programme outcome indicators before (2003-2005) and after (2006-2008) the GF grant.RESULTS: During the study period 293 TB cases were enrolled on treatment. Comparing the cumulative outcome indicators for smear-positive pulmonary TB cases 3 years before and after the grant, case notification increased by >50%, case detection by almost 50% and treatment success by nearly 20% during the grant period. The case detection rate for smear-positive pulmonary TB nearly doubled, while the treatment success rate reached 100% in 2006. Default and mortality rates dropped to zero in 2006 and 2007 from maximum values of respectively 15% and 23% in 2004 and 2005. However, in 2008, there was a decline across all programme indicators, probably due to staff turnover. CONCLUSION: Outcome indicators of the TB programme in BDH increased markedly following the implementation of the GF grant. Nevertheless, if not tackled appropriately, staff turnover might impede the sustainability of this positive outcome.
Gesehen am 19.12.2022